The Potential of White Tea (Camellia sinensis) and Kelor (Moringa oleifera) in Improving Lipid Profile and Histopathological Features of Pancreas in Streptozotocin-Induced Rats - Martini, Rina; Rahma, Amalia; Kusharto, Clara Meliyanti; Riyadi, Hadi; Sumantri, Cece; Rohdiana, Dadan (Jurnal Gizi dan Pangan, 2019)
This study aimed to examine the potential of white tea and kelor in improving lipid profile and histopathological features of the pancreas in streptozotocin-induced Sprague-Dawley rats. The research design was an experimental study with post-test control group design. Catechin content were analysed using High-Performance Liquid Chromatography. Twenty Sprague-Dawley rats (out of 24 rats, 12-week old, 200-300 g) were induced with intraperitoneal injection of streptozotocin at a dose of 40 mg/kg BW. Four groups of rats received one of the green tea (GT), white tea (WT), kelor (K), or the mixture of white tea and kelor (WTK) with a dose of epigallocatechin-3-gallate (EGCG) at 100 mg/kg BW administered orally for 21 days. Measurements of the lipid profile and preparation of histopathological features of the pancreas were performed after the intervention was completed. The results showed that white tea had the highest concentrations of catechin (39.17%), gallic acid (1.09%), EGCG (4.46%), and epicatechin (9.61%) compared to the other tea groups. The TG levels of the WTK group (95±19.35 mg/dl) were significantly different (p<0.05) from the WT and K groups but not significantly different from the normal (105.8±23.89 mg/dl), DM and GT groups. Meanwhile, the HDL levels did not show significant differences in each intervention group (p>0.05). The mean diameter of the islets of Langerhans in the DM group (9.16± 2.56 μm) was significantly different (p<0.05) from the WT (20±8.94 μm), K (17.16±5.26 μm), WTK (18.66±4.17 μm), and N (21.07±8.49 μm) groups but not significantly different from the GT group (14.33±5.24 μm). The histopathological features of the pancreas showed an increase in the diameter of the islets of Langerhans in WT, K, and WTK groups. This study revealed that the mixture of white tea and kelor had the potential to ameliorate triglyceride levels and histopathological features of the pancreas in streptozotocin-induced Sprague-Dawley rat.